Detection of Prosthetic Joint Infection Based on Magnetically Assisted Surface Enhanced Raman Spectroscopy - Fargašová, Ariana; Balzerová, Anna; Prucek, Robert; Sedláková, Miroslava Htoutou; Bogdanová, Kateřina; Gallo, Jiří; Kolář, Milan; Ranc, Václav; Zbořil, Radek (Analytical chemistry, 2017)
Accurate and rapid diagnosis of prosthetic joint infection (PJI) is vital for rational and effective therapeutic management of this condition. Several diagnostic strategies have been developed for discriminating between infected and noninfected cases. However, none of them can reliably diagnose the whole spectrum of clinical presentations of PJI. Here, we report a new method for PJI detection based on magnetically assisted surface enhanced Raman spectroscopy (MA-SERS) using streptavidin-modified magnetic nanoparticles (MNP@Strep) whose surface is functionalized with suitable biotinylated antibodies and then coated with silver nanoparticles by self-assembly. The high efficiency of this approach is demonstrated by the diagnosis of infections caused by two bacterial species commonly associated with PJI, namely, Staphylococcus aureus and Streptococcus pyogenes. The method's performance was verified with model samples of bacterial lysates and with four real-matrix samples of knee joint fluid spiked with live pathogenic bacterial cells. This procedure is operationally simple, versatile, inexpensive, and quick to perform, making it a potentially attractive alternative to established diagnostic techniques based on Koch's culturing or colony counting methods.
Keywords: infekce spojené s protézou; povrchové vlastnosti; magnetické jevy; Magnetic Phenomena; Streptavidin; lidé; streptavidin; Prosthesis-Related Infections; magnetické nanočástice; Magnetite Nanoparticles; Surface Properties; Spectrum Analysis, Raman; Ramanova spektroskopie; Humans